Enterprise information architecture of a Malaysian institute of higher learning management information system: an experience - Suhaimi, Mohd Adam; Abdullah, Zainatul Shima; Dahlan, Abdul Rahman; Sidi, Fatimah; A. Jabar, Marzanah; Ishak, Iskandar (2014)
In an institute of higher learning such as the university, developing the right information enterprise architecture is very important to provide the university to be sustainable in the higher learning environment. Previously built system which are developed solely created islands of system within the university and thus makes it hard to be integrated for better information and knowledge management system. This paper discusses the development of the Integrated Data Dictionary and Enterprise Information Architecture (IDEIA) framework for the International Islamic University Malaysia. The framework also consists of data strategy, data standardization process and corresponding implementation policies. It present the architecture direction and policies for all entities in a university that are planning or making changes or additions to their information system, that are constantly and dynamically gathered and processed to create information needed to support the university's business goals.